A history of early household economics: Improving the family's contribution to industrial production and rationalizing family consumption. (31st August 2020) - Bankovsky, Miriam
Abstract: This article contributes to our knowledge of two early phases in the history of household economics. The first is represented by the 19th-century theory of Alfred Marshall and the second by the interwar theories of several North American consumer economists (Hazel Kyrk, Elizabeth Hoyt, and Margaret Reid). The aim is to present the analytical focus and accounts of social good that animated these phases. Since Marshall's focus was on improving industrial production, his family economics explained how the Victorian family could improve the labour it contributed to industry. But the North American consumer economists sought to improve family consumption. Regarding ethics, 19th-century families were to cultivate an industrious and altruistic character. But the consumer economists thought families needed protection from producer fraud, along with living standards that expressed their individuality. Early household economics also accepted the gendered family form that had accompanied these developments, rejecting more 'activist' conceptions.